Menneisyyden kuvat, lasten pihaleikit Jyväskylän Seminaarinmäellä 1940-1950 -luvuilla - Suominen, Oona (2024)
In this thesis, I familiarize myself with the playground culture of the 1950s through photographs. I have received Ahti Rytkönen's photographs of children playing in the yard in the 1940s and 1950s on Seminaarinmäki in Jyväskylä from the science museum of the Open Science Centre. When examining these pictures, I answered two research questions: 1. How does Ahti Rytkönen's museum material represent the school yard games on Seminaarinmäki in the 1950s? 2. How do Ahti Rytkönen's photographs represent the cultural environment?